Bridging the Gap in Solid Waste Management : Governance Requirements for Results - World Bank (World Bank, Washington, DC, 2021)
**Revised edition published April 2022** The primary responsibility for providing on-the-ground services and for ensuring the controlled management of solid waste, on the other hand, lies with the local authorities. Often fiscally constrained with many competing priorities beyond waste, local authorities may have limited ability to deliver adequate services. Their technical and operational capacities may be stretched, resulting in sub-optimal arrangements for service delivery, or in poor engagement with stakeholders that are crucial to implementation of local services, including the general population and other waste generators, the private sector, and the informal sector. This paper discusses good practices for the governance of the solid waste management sector in a context of pressing need. The document is organized along seven chapters. Together, these chapters aim to give practical guidance on waste management governance to national and local authorities as well as practitioners.